2008
DOI: 10.1111/j.1471-4159.2008.05623.x
|View full text |Cite
|
Sign up to set email alerts
|

Different structural requirements for functional ion pore transplantation suggest different gating mechanisms of NMDA and kainate receptors

Abstract: Although considerable progress has been made in characterizing the physiological function of the high‐affinity kainate (KA) receptor subunits KA1 and KA2, no homomeric ion channel function has been shown. An ion channel transplantation approach was employed in this study to directly test if homomerically expressed KA1 and KA2 pore domains are capable of conducting currents. Transplantation of the ion pore of KA1 or KA2 into GluR6 generated perfectly functional ion channels that allowed characterization of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These “released” GluK5 receptors are non-functional, but it is not known why. Transplanting the pore sequence of GluK5 into the background of GluK2 gives small currents, suggesting that GluK5 itself could be permeation competent (Villmann et al, 2008). Furthermore, it is known that GluK5 subunits harbor a functional ligand binding domain, with high affinity for both kainate and glutamate (Barberis et al, 2008; Herb et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…These “released” GluK5 receptors are non-functional, but it is not known why. Transplanting the pore sequence of GluK5 into the background of GluK2 gives small currents, suggesting that GluK5 itself could be permeation competent (Villmann et al, 2008). Furthermore, it is known that GluK5 subunits harbor a functional ligand binding domain, with high affinity for both kainate and glutamate (Barberis et al, 2008; Herb et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…The strategy to reassemble functional receptor proteins from non-functional modules takes advantage of the domain architecture of ion channels. Domain swapping experiments between different ion channel subunits have been shown to preserve receptor function in various receptor families, such as the glycine receptor with the prokaryotic GLIC or different glutamate receptors (24,25). For GlyR, nonsense and frameshift mutations have been described in patients suffering from hyperekplexia, a rare neuromotor disorder (20,26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pore domain represents high homology to the ion channel domain of K + channels (Villmann and Becker, 2007). Several studies on domain swapping have shown that homologous domains can be exchanged between different receptor subclasses without dramatic changes in ion channel properties (Strutz et al, 2002; Hoffmann et al, 2006; Villmann et al, 2008). Reconstitution of functionality from independent folding domains seemed to be a chance to gain-of-function for truncated receptor proteins.…”
Section: Receptor Assembly From Independently Folding Domainsmentioning
confidence: 99%